2015
DOI: 10.1016/j.healun.2014.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Long-term functional benefits of human embryonic stem cell-derived cardiac progenitors embedded into a fibrin scaffold

Abstract: A fibrin scaffold loaded with ESC-derived cardiac progenitors resulted in sustained improvement in contractility and attenuation of remodeling without sustained donor cell engraftment. A paracrine effect, possibly on innate reparative responses, is a possible mechanism for this enduring effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 47 publications
1
52
0
3
Order By: Relevance
“…One current clinical trial is actively recruiting patients to test the use of human ESC-derived cardiac progenitor cells in patients with heart failure (NCT02057900) (119). On the basis of their preclinical data showing a significant improvement in cardiac function due to paracrine effects of the transplanted cardiac progenitor cells (120), this ongoing clinical trial is using fibrin patches containing Isl-1 + SSEA-1 + cells. The trial's first clinical case report has found improvement in patient's functional outcomes and evidence of new-onset contractility of the transplanted area (121).…”
Section: Applications Of Ipscsmentioning
confidence: 99%
“…One current clinical trial is actively recruiting patients to test the use of human ESC-derived cardiac progenitor cells in patients with heart failure (NCT02057900) (119). On the basis of their preclinical data showing a significant improvement in cardiac function due to paracrine effects of the transplanted cardiac progenitor cells (120), this ongoing clinical trial is using fibrin patches containing Isl-1 + SSEA-1 + cells. The trial's first clinical case report has found improvement in patient's functional outcomes and evidence of new-onset contractility of the transplanted area (121).…”
Section: Applications Of Ipscsmentioning
confidence: 99%
“…Also related to gestation, MSCs obtained from fetal heart tissue (fC-MSC) and embryonic stem cells (ESC) have been proposed as alternative multipotent cells with the ability to differentiate into CMs, endothelial and smooth muscle cells. However, the use of such cells is obviated by evident ethical dilemmas [52][53][54][55].…”
Section: Stem Cells Obtained From Pregnancy Byproducts and Other Gestmentioning
confidence: 99%
“…Also, they promote migration of endothelial cells and smooth muscle cells and, simultaneously, confer CMs protection from apoptosis. In addition, these materials have low immunogenicity and have anti-inflammatory and pro-angiogenic properties [17,18,20,37,50,53,67,107,108,112,115]. This explains why delivery of stem cells in scaffolds has higher benefits to those delivered in aqueous or in culture media, with regard to cell retention and proliferation as well as structural and functional myocardial recovery.…”
Section: Combination Of Different Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plusieurs équipes expérimentent l'application sur les zones pathologiques cibles des feuilles de cellules, ou de matrices cellularisées biodégradables à base d'alginates, de Matrigel, de fibrine, de polysaccharides, de gélatine, de collagène, dans différentes espèces animales (Souris, Rat, Cochon d'Inde, Mouton, Macaque) [29]. Certaines matrices favorisent la survie cellulaire et promeuvent l'angiogénèse locale, et dans des modèles post-ischémiques, ces greffons améliorent la fonction cardiaque [30,31]. Des progrès restent à accomplir concernant l'intégration réelle de ces biomatériaux, leur vascularisation, leur colonisation par des cellules de l'hôte, et réci-proquement la migration des cellules qu'elles contiennent vers le tissu cardiaque hôte.…”
Section: Délivrance Des Cellules Biomatériaux Et Suivi Des Cellulesunclassified